Pengaruh Penerapan Metode Debat Terhadap Aktivitas Belajar Pada Mata Pelajaran Fiqih Kelas X di Mas Muhammadiyah Lawang Tigo Balai - Charles Charles; Arman Husni; Al Baihaqi Anas; Retri Emilia Oktaviani (LP3M KH Yazid Karimullah Institute, 2023)
This research is motivated by the obsevations of researchers who found that learning conducted by teachers only uses the lecture method, so that students tend to only listen to what is conveyed by the teacher which results in no feedback which causes students to be less active in learning Fiqih. The purpose of this study was to find out how much influence the application of the debate method had on learning activities in class X Fiqih subjects at MAS Muhammadiyah Lawag Tigo Balai. The type of research used in this study is a quantitative approach, using a Quasy Experimental research design with The Non-equivalent Group Design. The students to be sampled were class X IPK as the experimental class and class X IPS as the control class. The students to be sampled were class X IPK as the sampling technique was to collect data on students’ daily scores, after which a normality test and homogeneity test were carried out. After confirming that they were normal and homogeneous, the researcher determined randomly for the experimental class and the control class. In this study the instrument of student learning activities will be used. Based on the research results obtained tcount = 11,114 ˃ 2,024 and sig. (2-tailed) 0,00 ˂ 0,005. Then the hypothesis is accepted which states that there is a significant influence between the debate method and conventional lerning methods, it means that Ho is rejected. So it can be concluded that there is a significant influence of the debate method on learning activities in class X Fiqih subjects at MAS Muhammadiyah Lawang Tigo Balai.